Improvement of methods for estimation of catchability for trawl survey systems with use of hydroacoustic means (on example of walleye pollock in the Okhotsk Sea) - Mikhail Yu. Kuznetsov; Vladimir I. Poljanichko; Igor A. Ubarchuk (Известия ТИНРО, 2015)
In commercial fishery, catching properties of fishing gears are developed mostly for effective catch of fish, rather than for precise measurement of fish distribution density in water, so a problem of catchability exists and this parameter should be determined for each fishing gear. Various methods for estimation of catchability for trawl survey systems are considered. The experimental method of its estimation (comparing of fish density in towed volume determined by other tools with trawl catch) is considered as the most authentic. Scheme and algorithm of the measurements and calculations are described for standard hydroacoustic tools, as scientific echosounder ЕК-60, and software is developed for recalculation of trawl catch to equivalent acoustic units of fish density in the towed volume of water. Results of the catchability estimation for the trawl RT/TM 57/360 used for walleye pollock stock assessment in the Okhotsk Sea are analyzed. Mean value of the catchability coefficient in this case varies from 0.42 to 0.81, generally increasing with depth but decreasing both at the sea surface and on the depth > 200 m. These results correspond well with the model of fish behavior in the noise field of vessel: the low catchability at the sea surface and its increasing with depth could be caused by avoiding reaction of fish to the noise and its moving to deeper layers. Besides, the catchability coefficient for pollock depends on fish size and time of day: it increases with the fish length but decreases for the largest individuals. Influence of the noise field of vessel on selectivity of survey trawls is modeled and there is shown that the depths of the maximum concentration of small-sized and large-sized pollock do not coincide. The developed software and received results are universal means for estimation of the catchability for trawls in all conditions of trawling, they allow to choose optimum mode for survey trawling in dependence on fish species, depth of trawling, and type of vessels and trawl.